An empirical of managerial value systems and decision-making styles among the managers in Iran. - Amirshahi, Mirahmad (Curtin University, 1997)
The main purpose of this research is to identify the value systems and decision-making styles of Iranian managers. The relationships between their value systems and decision styles, and between their value systems and certain demographic variables (such as level of education, social group, etc.) and organizational variables (such as company size, kind of ownership, etc.) are also investigated. Both quantitative and qualitative methods are applied in this study and the following analyses are undertaken:a one-way univariate and multivariate analysis of variance (ANOVA and MANOVA) are used to test the hypotheses developed in Chapter 1.Mean differences are examined, using multiple discriminant analysis (MDA), when significant results are obtained.Pearson Partial Correlation analysis is performed to elucidate the relationships between the managerial value systems and their status of individualism/collectivism.Case study analysis is conducted for an in-depth investigation into the data.In the quantitative portion of the study, a sample of 768 managers in various organizations was surveyed. Statistical analysis of the survey data classified managerial value systems into tribalistic, egocentric, conformist, manipulative, sociocentric, and existential. This classification was conducted in accordance with the framework developed by Flowers et al. (1975). Furthermore, following Ali's questionnaire (1993), managerial decision-making styles were classified into autocratic, pseudo-consultative, consultative, participative, pseudo-participative, and delegative.The findings indicate that an average Iranian manager represents a mix of all six value systems in roughly equal proportions. The data suggests that a conformist orientation is the dominant value system of Iranian managers followed by sociocentric values, with egocentric values the least dominant. As for the decision styles, more than one half of Iranian managers (55%) practice consultative means of decision-making, followed by 21 % who are proponents of participative style, and 15% who are pseudo-participative. Delegative, autocratic and pseudo-consultative decision styles are the least preferred in Iran. The relationship between value systems and decision-making styles revealed that highly collectivist managers are more participative while highly individualistic managers are more autocratic in their decision-making style. The results also suggest that the higher their level within the hierarchy, the more likely managers are to be delegative and autocratic, and the less likely they are to be participative and consultative than their colleagues in the lower levels of managerial hierarchy.A comparative cross-cultural analysis of the managerial value systems and decision-making styles of Iranian managers with their counterparts in other Middle Eastern countries was also undertaken. The results indicate that overall the dominant value systems of managers from the Middle East are conformist, sociocentric and existential, with egocentric and manipulative being the least prevalent. Furthermore, their dominant decision-making style is consultative, with autocratic and delegative styles being the least prevalent. Compared with the other Middle Eastern managers, Iranian managers are more conformist and tribalistic and less sociocentric and existential. Furthermore, Iranian managers are more consultative, more delegative, more participative, and significantly less pseudo-consultative, compared with managers from other Middle Eastern countries.The qualitative portion of this study comprises two extensive case studies of exemplary Iranian organizations, i.e., Tehran Municipality and Watt Meter Company of Iran. The main objective of these case studies is to provide in-depth data as a supplement to the broad based analysis of the questionnaire survey. They also give a different perspective, resulting from a multidisciplinary integrative inquiry. The required data for writing the cases was collected through the companies' records, field observations, and one-to-one and focus group interviews with various levels of their management team, as well as their employees and customers. Both primary and secondary data were then used in writing the case studies. Qualitative analysis of the case studies suggests that advanced management practices like decentralization, delegation of authority, out-sourcing, detailed planning, total quality management, effective human resource management and strategic management, which are more widely used in the industrialized countries, could be used with effectiveness in Iran despite its cultural differences. This finding supports Ralston et al. (1993) and both "convergence" and "divergence" views toward management practices and suggests that advanced management practices and continuous attention to human resource management may, as the case of the Watt Meter Company implies, create an effective corporate culture that fosters change.The leader's role is a very important variable in the issue of the cross-cultural transmission of management practices - especially in collectivistic societies like Iran and the rest of the Middle Eastern countries. In these societies, individuals and organizations identify strongly with their leaders. This is mainly due to their historical, socio-cultural and Islamic traditions and values. The case studies suggest that in traditional, hierarchical, and collectivistic societies like Iran, to be effective, organizational change should start from the very top. The vital common variables for success are visionary leadership with clear direction, effective human resource management, and empowerment of the workforce. All these seem to be essential for building the required corporate culture that fosters change.As the first study to measure the value systems and decision-making styles of Iranian managers, it contributes to the management literature in Iran and the Middle East. It builds upon:Flowers' et al (1975) contentions regarding the construct of managerial value systems;Hofstede's (1980) theory of national culture, which attempts to identify the cultural characteristics of members of various countries;Ronen and Shankar's (1985) principles for grouping countries based on their religion, language, and geography; andThe convergence versus divergence controversy regarding the cross-cultural transmission of management practices.This research is among the very few studies which investigates the characteristics of Iranian managers, i.e., their value systems and decision styles. It is widely believed that the business philosophy of any country depends, to a large degree, upon the values held by those in management. The present study is, thus, a detailed introduction to contemporary Iran and the way it is managed.